Idiopathic erythrocytosis in a patient on chronic hemodialysis - Dong Hyun Lee; Ji Hye Min; Sang Byung Bae; Hyo Wook Gil; Jong Oh Yang; Eun Young Lee; Sae Yong Hong (The Korean Society of Nephrology, 2015)
A 78-year-old man on hemodialysis presented to our hospital with erythrocytosis. He had started hemodialysis 4 years previously, with a hemoglobin level of 9.8 g/dL, and was administered erythropoiesis stimulating agents and ferrous sulfate. Two years previously, his hemoglobin level increased to 14.5 g/dL and the treatment for anemia was discontinued. He continued hemodialysis thrice weekly; however, the hemoglobin level had increased to 17.0 g/dL at the time of presenting to our hospital. His serum erythropoietin level was 31.4 mIU/mL (range, 3.7-31.5 mIU/mL), carboxyhemoglobin level was 0.6% (range, 0-1.5%), and oxygen saturation in ambient air was 95.4%. The JAK2 V617F mutation was not observed and other bone marrow abnormalities were not identified. The patient was diagnosed with bladder cancer and a transurethral resection was performed. Eight months after the treatment of bladder cancer, his hemoglobin level was 15.1 g/dL, and he was diagnosed with idiopathic erythrocytosis.